130k views
5 votes
Hellpp -4c - 9.6 +5c = 0

User Steffi
by
5.2k points

2 Answers

0 votes

Answer:

c = 9.6

Explanation:

Let's look at our equation; - 4c - 9.6 + 5c = 0. Now we need to collect the like terms which are -4c and 5c.

- 4c - 9.6 + 5c = 0

5c - 4c - 9.6 = 0

We get: c - 9.6 = 0

Now we will add 9.6 on each side to see what c is equal to.

c - 9.6 = 0

+9.6 +9.6

c = 9.6

Yay! We got our answer! Nice job everyone!

User Juagicre
by
5.2k points
6 votes

Answer:

c =9.6

Explanation:


-4c - 9.6 +5c = 0\\\\\mathrm{Group\:like\:terms}\\-4c+5c-9.6=0\\\\\mathrm{Add\:similar\:elements:}\:-4c+5c=c\\c-9.6=0\\\\\mathrm{Add\:}9.6\mathrm{\:to\:both\:sides}\\c-9.6+9.6=0+9.6\\\\Simplify\\c=9.6

User Optimisticupdate
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.